2021
DOI: 10.1186/s13018-021-02498-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aqueous extract of Prunus dulcis on tibial bone healing in the rabbit

Abstract: Background Bone fractures are medical emergencies that require prompt intervention to help return bone to its normal function. Various methods and treatments have been utilized to increase the speed and efficiency of bone repair. This study aimed to investigate the treatment effects of Prunus dulcis aqueous extract on tibial bone healing in rabbits. Methods All animals were distributed in five groups with six rats in each group, including the sham … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…A previous study had reported that the increase in blood calcium causes more calcium-phosphate crystals to deposit at the defect site and thereby defect closure occurs faster. [41] These results are consistent with those of our study, which suggests that the synergistic effect of LDH, gelatin, and diosgenin leads to faster healing of the tibial defect.…”
Section: Serum Calcium Phosphorus and Alkaline Phosphatase Measurementsupporting
confidence: 93%
“…A previous study had reported that the increase in blood calcium causes more calcium-phosphate crystals to deposit at the defect site and thereby defect closure occurs faster. [41] These results are consistent with those of our study, which suggests that the synergistic effect of LDH, gelatin, and diosgenin leads to faster healing of the tibial defect.…”
Section: Serum Calcium Phosphorus and Alkaline Phosphatase Measurementsupporting
confidence: 93%
“…Alkaline phosphatase is an important marker for bone formation as it is secreted by osteoblasts. This enzyme stimulates the mineralization of the osteoid by raising the local concentration of calcium phosphate as mentioned by Anaraki et al (2021 ).…”
Section: Alkaline Phosphatase Levels (Iu/l)mentioning
confidence: 98%
“…In animal studies, amlodipine ( 114 ), cilostazol ( 115 ), L-arginin ( 116 ), sildenafil ( 117 ), and metformin ( 118 ) were shown to facilitate fracture healing. Aditionally, irisin ( 119 ), tumeric acid ( 120 ), aqueous extract of Prunus dulcis ( 121 ), and the Chinese acupuncture and herbal formula powder prescription ‘Zhèng Gŭ Zĭ Jīn Dān’ ( 122 ) are thought to accelerate fracture healing, but this has not yet been shown in clinical studies with patients and with an appropriate study design.…”
Section: Pharmacologic Interventionsmentioning
confidence: 99%